Functional Outcome of Intercondylar Distal Humerus Fractures Surgically Treated with Open Reduction and Internal Fixation with a Principle Based on Orthogonal Plating Technique - Thapa, Santosh; Jha, Ranjib Kumar; Rajthala, Ashish (Birat Journal of Health Sciences, 2021)
Introduction: Owing to the complex articular structure, paucity of metaphyseal bone and thin soft tissue covering, treatment of intra-articular distal humerus fractures still pose challenge to surgeons. Although it comprises 2% of all fractures the massive complication rate to the treatment is worrisome. This study aims to evaluate the outcome of surgical treatment of these fractures by open reduction and internal fixation by dual orthogonal plates. Objectives: The objective of the study is to evaluate the functional outcome of intercondylar humerus fractures managed with open reduction and internal fixation with orthogonal dual plating technique. Methodology: Eighteen patients (19 – 68 years old) with AO/OTA type 13C fractures were evaluated after surgery for one year with MEPS and range of motion. Complications were categorized as major or minor complications. Functional comparisons were made between simple articular type C1/C2 and complex articular type C3 fractures at one year. Result: There were 2 (11.11%) type C1 fracture and 8 (44.44%) each in type C2 and C3 fractures. Eight (44.44%) patients obtained excellent, 7 (38.89%) obtained good and 3 (16.7%) obtained fair results. There was no poor outcome. Average MEPS score was 83.33 and there was no significant between the subgroups (p = 0.07). The average flexion was 118.06° and it was significantly impaired in type C3 fractures (p = 0.03). Three patients obtained full extension, and remaining patients had mean extension deficit of 12°. Average arch of motion was 108.06° with significant difference between two subgroups (p = 0.008). The mean arc of motion for supination-pronation was 154.44°. There was 5 minor and 2 major complications (total - 38.9%). Conclusion: The surgical management with open reduction and internal fixation by dual plates in orthogonal configuration for the intercondylar distal humeral AO type C fractures has good or excellent functional outcome in majority of the patients.